Valuasi Ekonomi Kawasan Ekowisata Mangrove Berkelanjutan di Pantai Indah Kapuk Jakarta Utara - Berlianty, Ina; Yudha, Eka Purna; Nuryati, Rina (Universitas Galuh, 2026)
Mangrove ecotourism contributes significantly to supporting coastal ecosystems, both economically and ecologically. The objective of this study is to identify the current condition of the mangrove forest in the Mangrove Ecotourism Area of Pantai Indah Kapuk (PIK) and to conduct an economic valuation of environmental services and the potential for sustainable ecotourism. The analysis used is a mix method by combining quantitative and qualitative approaches. The techniques used for data collection include surveys, observation, interviews, and documentation. The economic valuation is conducted using the Total Economic Value (TEV) approach, which includes direct use value, indirect use value, option value, existence value, and bequest value. The results show that the PIK mangrove ecotourism area provides significant economic contributions through various environmental services and ecotourism activities, although its management still faces several challenges, such as environmental degradation, limited facilities, and low community participation. The calculated economic value can serve as a basis for formulating sustainable and inclusive ecotourism management policies, in line with the Sustainable Development Goals (SDGs).